Self-Schedule and Self-Distributive MAC Scheduling Algorithms for Next-Generation Sensor Networks - Bakhsh, S.T. (Hindawi Publishing Corporation, 2015)
The distributive nature of wireless sensor networks (WSNs) poses great challenges for the design of distributive scheduling to maximize network life and spatial reuse of time slot with minimum frame length. Most of the existing scheduling techniques are either centralized or contentional. The existing techniques cannot efficiently adapt to the dynamic wireless environment. In this paper, self-scheduled and distributed MAC (SSD-MAC) and self-distributive MAC (SD-MAC) medium access control algorithms are proposed to reduce the complexity and variety of scheduling problems. The proposed algorithms do not require any synchronization and can effectively adapt to dynamic topology changes without incurring global communication overhead. According to the proposed algorithms, each node maps a conflict-free time slot for itself up to 2-hop neighboring nodes. Consequently, each node successfully schedules a unique time slot for itself in a heuristic manner based on its local information. Moreover, the proposed algorithms also guarantee conflict-free edge coloring because all the incident edges to a single node are assigned to colors in such a way that none of the edges should have the same color. It has been demonstrated that, with regard to communication overhead, energy consumption and execution time through simulation proposed that algorithms outperform existing distributed randomized scheduling algorithm (DRAND). Â© 2015 Sheikh Tahir Bakhsh et al.